La ciencia Antropológica en la formación general - Munizaga, Carlos (Revista Chilena de Humanidades, 2016)
The author refers to the usefulness of Anthropology for the affective and the cognitive development of man. He proceeds to recollect personal experiences of close approach to other disciplines in an anthropological perspective. The significance of such a science is pointed out insofar as it leads toan understanding of culture, the variability of societies, of small social units and, in general, of different human groups. His central thesis finds exemplification in the references to family, dwelling, and games.